2016
DOI: 10.1088/0957-4484/27/30/302001
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of silk: the fundamentals of a strong, tough and versatile material

Abstract: Spider silk is a remarkable material that provides a template for upscaling molecular properties to the macroscale. In this article we review fundamental aspects of the mechanisms behind these behaviors, discuss the molecular makeup, chemical designs, and how these integrate in a complex arrangement to form webs, cocoons and other material architectures. Moreover, this review paper explores the unique ability of silk to tolerate various kinds of defects, in a way enabling this material platform to serve as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 110 publications
1
48
0
Order By: Relevance
“…3 and 4, Figure g), whereas the PVA/Alg/HAP hybrid macrofiber has no yield point. In general, the yield point of natural SSF is reached along with the stretching of the tough non‐crystalline protein block, and then, the crystalline protein block is used to dissipate the applied stress energy . In our hybrid macrofiber system, the hybrid macrofiber is constructed by numerous tightly stacked microfibers, which are mineralized with HAP nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4, Figure g), whereas the PVA/Alg/HAP hybrid macrofiber has no yield point. In general, the yield point of natural SSF is reached along with the stretching of the tough non‐crystalline protein block, and then, the crystalline protein block is used to dissipate the applied stress energy . In our hybrid macrofiber system, the hybrid macrofiber is constructed by numerous tightly stacked microfibers, which are mineralized with HAP nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…to glue sheets of cellulose together, giving high toughness during mechanical testing (18). This is interesting because high toughness is a characteristic property of natural spider silk proteins (29). We found that the toughness provided by CBM-ADF3-CBM was connected to the way it was assembled.…”
Section: S C I E N C E a D V A N C E S | R E S E A R C H A R T I C L Ementioning
confidence: 86%
“…(Federici et al 2001;Smirnov et al 2015;Glaser et al 2006;Pan et al 2016;Ma et al 2017), mainly due to its high melting point, excellent high-temperature mechanical properties, good sputtering resistance, and low deuterium/tritium retention (Yih and Wang 1979;Chen et al 2008;Wang et al 2016;Yang et al 2016). It is well known that the nano-sized materials possess much better electronic, mechanical, and chemical properties than the traditional bulk materials (Mistry et al 2016;Tian et al 2013;Salorinne et al 2016;Gilbert et al 2004;Zhu et al 2016;Monti et al 2016;Guo et al 2015;Su and Buehler 2016;Qi et al 2009;Qi and Lee 2010). In this respect, various nano-sized W samples have been fabricated experimentally by means of such techniques as mechanical alloying and single damascene process flow (Steinh gl et al 2005;Wang et al 2007;Yeong and Thong 2006).…”
Section: Introductionmentioning
confidence: 99%